Determinants of comprehensive HIV and AIDS knowledge among Tanzanian adolescent girls and young women: a multilevel application of Andersen’s behavioral model based on national survey - Bago, Mussa Hassan; Stephano, Elihuruma Eliufoo; Kessy, Sahnun Ally; Tibenderana, Jovin R.; Godfrey Majengo, Victoria; Oguma, Erick Donald; Mwalingo, Tegemea Patrick; Kessy, Immaculata P.; Nyundo, Azan Abubakar; Mtoro, Mtoro J. (Frontiers in Public Health, 2025)
BackgroundLimited comprehensive HIV and AIDS knowledge is a significant factor contributing to the prevalence of HIV among adolescent girls and young women (AGYW). Therefore, this study aimed to determine the level of comprehensive HIV and AIDS knowledge and identify its associated factors among AGYW in Tanzania.MethodsAn Analytical cross-sectional study of the 2022 Tanzania Demographic and Health Surveys data was conducted. The study included 5,810 AGYW, selected through a two-stage sampling method. Multilevel logistic regression, accounting for the complex survey design, was used to identify individual and community-level factors associated with comprehensive HIV/AIDS knowledge. Analyses were conducted using Stata 18.5. Adjusted odds ratios (AORs) with 95% confidence intervals (CIs) were reported, and statistical significance was set at p < 0.05.ResultsThe prevalence of comprehensive HIV and AIDS knowledge among AGYW was 46.2% (95% CI: 44.3–48.2%). In the final fitted multivariable analyses, AGYW in primary (AOR = 1.97, 95%CI: 1.56–2.47), secondary (AOR = 3.79, 95%CI: 2.96–4.85), AGYW in a rich quantile (AOR = 1.38, 95%CI: 1.15–1.66), owning a mobile phone (AOR = 1.26, 95%CI: 1.09–1.45), the use of the internet (AOR = 1.40, 95%CI: 1.16–1.68) and AGWY who ever tested for HIV (AOR = 1.61, 95%CI: 1.39–1.87) had higher odds of having comprehensive knowledge compared to their counterparts. At the community level, geographical zones exhibited higher odds of having comprehensive knowledge.ConclusionDespite notable progress in HIV education, gaps persist, especially among AGYW, underscoring the need for focused, diversified interventions. By advancing understanding of these determinants, the study provides crucial evidence to inform tailored HIV prevention strategies aimed at enhancing knowledge and reducing infection rates within this vulnerable population and improving safer sex practices.